Need for insulin to control gestational diabetes is reflected in the ambulatory arterial stiffness index - Kärkkäinen Henna; Laitinen Tomi; Heiskanen Nonna; Saarelainen Heli; Valtonen Pirjo; Lyyra-Laitinen Tiina; Vanninen Esko; Heinonen Seppo (BMC, 2013)
Abstract Background The aim was to evaluate the metabolic profile in conjunction with vascular function using the ambulatory arterial stiffness index (AASI) in women with uncomplicated pregnancies and in women with gestational diabetes mellitus (GDM). Methods Plasma glucose, lipids, HOMA -IR (homeostasis model assessment of insulin resistance) and AASI, as obtained from 24-hour ambulatory blood pressure monitoring in third trimester pregnancy and at three months postpartum, were measured in three groups of women: controls (N = 32), women with GDM on diet (N = 42) and women with GDM requiring insulin treatment (N = 10). Results Women with GDM had poorer glycemic control and higher HOMA-IR during and after pregnancy and their total and LDL (low density lipoprotein) cholesterol levels were significantly higher after pregnancy than in the controls. After delivery, there was an improvement in AASI from 0.26 ± 0.10 to 0.17 ± 0.09 (P = 0.002) in women with GDM on diet, but not in women with GDM receiving insulin whose AASI tended to worsen after delivery from 0.30 ± 0.23 to 0.33 ± 0.09 (NS), then being significantly higher than in the other groups (P = 0.001-0.047). Conclusions Women with GDM had more unfavorable lipid profile and higher blood glucose values at three months after delivery, the metabolic profile being worst in women requiring insulin. Interestingly, the metabolic disturbances at three months postpartum were accompanied by a tendency towards arterial stiffness to increase in women requiring insulin.